Exploring New Sources of Economic Growth Amid The Covid-19 Pandemic - Moh Reza Firmansyah; Jamaluddin Iskandar; Ismawati Abbas (Fakultas Ekonomi dan Bisnis Islam UIN Alauddin Makassar, 2021)
Economic growth as a macroeconomic indicator that becomes a benchmark for a region can be seen from the increase in the income per capita of its population and the increase in production activities in various economic business fields. The magnitude of the economic potential of Makassar City is not directly proportional to the existing economic growth. The government seems unable to reproduce new sources of growth and this is exacerbated by the post-Covid-19 virus exposure. This is a problem for accelerating the city's economic growth. The novelty of this research tries to explore further the potential sources of new economic growth in Makassar City which is seen from sectoral contributions, namely the education sector, tourism sector, industrial sector, and trade sector. The purpose of this study describes the influence of the contribution of the education sector, tourism sector, industrial sector, and trade sector on economic growth in Makassar City. The data used in this study is secondary data obtained from the Central Statistics Agency in Makassar City. The analysis technique used is multiple linear regression analysis with the help of SPSS 23 software. The results show that the variables of education, industry, and trade have a positive and significant impact on economic growth in Makassar City. However, the tourism sector has no effect on economic growth in Makassar City. The implication of the research is that the government should strive to increase economic growth, by accelerating potential productive sectors, as the findings of this research, namely the education, trade and industry sectors, as a new source of economic growth for Makassar City. This is the focus so that in the future the city's economy will improve and become part of the economic recovery strategy agenda after the Covid-19 case. Keywords: Covid-19; Education; Growth; Industry; Trading